Neuroinflammation and comorbidities are frequently ignored factors in CNS pathology - Sandu, Raluca Elena (Neural Regen Res, 2015)
Virtually all drug interventions that have been successful pre-clinically in experimental stroke have failed to prove their efficacy in a clinical setting. This could be partly explained by the complexity and heterogeneity of human diseases as well as the associated co-morbidities which may render neuroprotective drugs less efficacious in clinical practice. One aspect of crucial importance in the physiopathology of stroke which is not completely understood is neuroinflammation. At the present time, it is becoming evident that subtle, but continuous neuroinflammation can provide the ground for disorders such as cerebral small vessel disease. Moreover, advanced aging and a number of highly prevalent risk factors such as obesity, hypertension, diabetes and atherosclerosis could act as “silent contributors” promoting a chronic proinflammatory state. This could aggravate the outcome of various pathological entities and can contribute to a number of subsequent post-stroke complications such as dementia, depression and neurodegeneration creating a pathological vicious cycle. Moreover, recent data suggests that the inflammatory process might be closely linked with multiple neurodegenerative pathways related to depression. In addition, pro-inflammatory cytokines could play a central role in the pathophysiology of both depression and dementia.